753 views
1 vote
Simplify this expression ( 2-5 square root 6) x 3 square root of 2

2 Answers

6 votes

6Г2-30Г3 D

Explanation:

User Basuro
by
5.7k points
4 votes

Answer:
6√(2)-30√(3)

Explanation:

Remember that:


(√(a))(√(b))=√(ab)


\sqrt[n]{a^n}=a

Given the following expression:


(2-5√(6))(3√(2))

The steps to simplify this expression, are:

1. Apply the Distributive property:


=(2)(3√(2))-(5√(6))(3√(2))=6√(2)-15√(12)

2.Since:


12=2*2*3=2^2*3

You can rewrite the radicand 12 in this form:


=6√(2)-15√(2^2*3)

3. Simplifying, you get:


=6√(2)-(15)(2)√(3)=6√(2)-30√(3)

4. Notice that the indices of the Radicals are the same, but the radicands don't, then, you can subtract the Radicals.

User LogicLooking
by
6.1k points